ANALISIS HASIL BELAJAR PESERTA DIDIK DALAM MENYELESAIKAN SOAL BANGUN RUANG SISI DATAR - Khasana, Nabila Nurul; Yusri, Radhya; Melisa (Universitas Insan Budi Utomo, 2026)
This study was based on the low learning outcomes of students in solving problems related to flat-sided shapes. The purpose of this study was to determine the learning outcomes of students in class IX.7 at SMPN 5 Padang in solving problems related to flat-sided shapes. The method used in this study is descriptive with a quantitative approach. The study subjects were selected using purposive sampling, with a sample size of 25 students. The instrument used in this study is a learning achievement test. Student learning outcomes were analyzed using a 4-point scale covering three indicators, namely: (1) the ability to write down the aspects known in the questions, (2) the ability to answer the questions, and (3) the ability to conclude the problems in the questions. The selection of study subjects was based on the number of students, categorized by their abilities: two students with very high abilities, two students with high abilities, two students with moderate abilities, two students with low abilities, and two students with very low abilities. Based on the test analysis results, it was found that 32% of students achieved high learning outcomes, 28% achieved moderate learning outcomes, 28% achieved low learning outcomes, and 12% achieved very low learning outcomes. Students with high learning outcomes tended to make mistakes in the indicator of the ability to summarize problems. Students with moderate criteria were less careful in answering questions and did not solve problems accurately. Students with low criteria often made mistakes in answering questions and solving problems. Meanwhile, students with very low criteria had difficulty writing down the known aspects of the question, answering questions, and correctly concluding problems.